Changes of the cardiac electrical cycle in type 1 diabetes during hypoglycaemia – a prospective observational study - Kézdi, Árpád; Horváth, Viktor J.; Vass, Viktor; Svébis, Márk M.; Kocsis, Győző; Ferencz, Viktória; Jávorfi, Tamás; Domján, Beatrix A.; Tabák, Ádám G. (Frontiers in Endocrinology, 2026)
IntroductionThe “dead-in-bed” syndrome is thought to be a consequence of hypoglycaemia-induced QTc prolongation in type 1 diabetes. Thus, we characterized electrocardiogram (ECG) changes during hypoglycaemia in healthy, free-living patients with type 1 diabetes without major comorbidities.MethodsA cohort of n=23 patients with type 1 diabetes wore continuous subcutaneous glucose and ECG monitors for approximately 7 days. We compared the frequency of ventricular premature beats (VPBs), the mean and SD of heart rate, and ECG intervals during hypoglycaemic episodes and their respective control episodes (n=226 episodes; n=1,697,205 beats) using linear mixed models.ResultsThe mean duration of hypoglycaemic episodes was 159 min (95% CI: 128–192) at night and 66 min (95% CI: 57–75) during the day. No differences in any of the investigated parameters were found between hypoglycaemic and control episodes during the day, nor in the frequency of nighttime VPBs. In contrast, the mean corrected QT (QTc) interval (mean difference (MD): 5, 95% CI: 2–9 ms) and the SDs of RR (MD: 17, 95% CI: 4–31), P-wave (MD: 2, 95% CI: 0–4), PQ (MD: 3, 95% CI: 1–6), QT (MD: 4, 95% CI: 2–7), and QTc intervals (MD: 5, 95% CI: 2–8) increased during nighttime hypoglycaemia.DiscussionDaytime hypoglycaemia is an unlikely cause of malignant arrhythmias in healthy patients with type 1 diabetes. The minimal increase in the QTc interval alone does not suggest an increased risk of malignant arrhythmias. However, the increase in the mean QTc together with an increase in its SD during nighttime hypoglycaemia is compatible with the extremely rare occurrence of the “dead-in-bed” syndrome.